Los actores locales de la modernidad a finales del siglo XIX: expositores poblanos en las exhibiciones mundiales. - María de Lourdes Herrera Feria (Nuevo mundo - Mundos Nuevos, 2009)
The research on elements and ways in which Mexico and its regions participated in the exhibitions is a valuable inventory of natural and human resources as well as of social, scientific and technical progress; so far, historical studies on the subject focused on the actions of elites located in the central government of the country and neglected the regional specificities in the periphery of the central power. In this paper, we are interested in presenting contribution of the State of Puebla to the Mexican pavilions at the international exhibitions and the participation of local actors in this collective enterprise. Our sources come from the Branch for the Promotion of the National Archives and public archives from the State of Puebla.